Incidence, severity and outcomes of hypoxemia in paediatric emergencies seen at a tertiary hospital in Southern Nigeria - Abiodun, Moses T.; Oziegbe, Gabriel; Mbarie, Imuwahen A.; Osarogiagbon, Wilson O.; Etin-Osa, Collins E.; Oluwafemi, Rosena O.; Okungbowa, Godwin E.; Ewhe, Ovonomo; Olusola, Rahmon; Nandom, Benjamin; Kpongo-Ogieva, Adesuwa; Aghama, Jane; et al. (International Journal of Contemporary Pediatrics, 2025)
Background: Hypoxemia refers to a low oxygen level in the blood, and is a significant morbidity in children. We evaluate the incidence, severity and outcome of hypoxemia as well as the prognostic usefulness of selected features in hypoxemic children. Methods: This was an analytic, cross-sectional study. Participants were acutely-ill children. Data were collected on their demography, clinical features, pulse oximetry, diagnoses and outcomes. Descriptive and inferential analyses were done. Multiple logistic regression identified variables that independently predict hypoxemia and outcomes of the participants, using odds ratio (OR) and 95% confidence intervals (CI). Results: Four hundred and seventy-six children participated in the study with a median (IQR) age of 2.0 (0.92–6.0) years; female: male ratio was 1:1. The incidence of hypoxemia was 59.2%; 96 (20.2%) were classified as mild, 62 (13.0%) as moderate and 124 (26.0%) as severe. Children aged 1–5 years were significantly more likely to have hypoxemia compared to those older than five years (OR=0.588, 95% CI: 0.358–0.964, p=0.035). Acute exacerbation of bronchial asthma showed a statistically significant association with hypoxemia severity (χ²=13.616, p<0.001). A majority (89.9%) of the participants survived. The overall outcome of participants varied significantly based on SpO₂ levels (p=0.025). Severe hypoxemia was strongly linked to mortality (95% CI: 1.292–6.615, p=0.010). Conclusions: Hypoxemia is common in childhood emergencies. Age of the affected child and nature of underlying disease as well as the severity of hypoxemia influence overall survival.